Lei de responsabilidade fiscal e finanças públicas: impactos sobre as despesas com pessoal e endividamento nos estados brasileiros - Soares, Cristiano Sausen (2013)
The main objective of this study is to identifythe impacts of theFiscal Responsibility Law(LRF) in the behavior ofpersonnel expensesandpublic debt, through statistical analysis parametric and non-parametric, and the use of the method analysis of panel data. The period of analysis refers to the years 2000 to 2010 for 26 states. In accordance with Complementary Law 101/2000, personnel expenses can not exceed 60% of Net Current Revenue (RCL), while the debt of these entities may not exceed 2 times the net current revenue. Initially, the indicator for control of personnel expenses is obtained by dividing the total personnel expenses by net current revenue. The analysis of these results was performed by comparing the averages over the period studied, indicating that the states are in agreement with LRF, with averages below 60%. However, it is clear that public entities that were well below this rate, increased their spending compromentendo state resources. To identify the position of the indebtedness of Federation Units were initially collected the data in the LC 101/2000 as indicators to control the debt of public entities, defined by the ratio Consolidated Net Debt and Net Current Revenue. The results indicate that, in general, states are in compliance with the limits defined in the LRF to indebtedness was indicated that in 2010 only the state of Rio Grande do Sul had indicator above the limit of 2 times the RCL. After we selected studies on the topic that pointed variables that could interfere with the behavior of the debt of these entities. This collection formed the basis for the construction of an econometric model that uses the analysis of panel data to estimate among those variables selectional significantly influence the behavior of the states debt. In this sense, it was identified that the indebtedness of the units of the federation can be explained by the variation of the debt itself lagged, the variation in investment spending of the states, for inflation and a dummy variable that indicates election years like those in the debt tends to rise. These results corroborate previous studies, especially regarding the relationship between debt and election years. estimating that in times of elections, public entities raise their spending, compromising subsequent budgets. Thus, this paper concludes that since the beginning of the term of LRF by 2010, Federation Units maintain efforts to conform to the limitations impositive this law, both in personnel expenses, and in debt